A new model for analyzing antimicrobial peptides with biomedical applications - Beschin, Alain; Bilej, M. (NATO science series. Life and behavioural sciences, 2002)
This volume first presents evidence for the earthworm's immune system; the results strongly suggest that certain molecules of the earthworm's immune system may be exploited as natural antibiotics - thus the biomedical applications.